Soil physicochemical properties under eucalyptus tree species planted in alley maize cropping agroforestry practice in Decha Woreda, Kaffa zone, southwest Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2021)
Different studies have shown that the effect of eucalyptus trees on soil physicochemical properties is variable, which indicates that more investigations that focus on different specific geographical locations and eucalyptus tree species are required. The objectives of this study was to evaluate the status of soil nutrients under four eucalyptus tree species planted in hedgerow system in comparison with that in its adjacent open land. To achieve these objectives, soil samples were taken from a soil depth of 0-20 cm from 15-20 spots by using auger and composited for respective treatments. Each soil samples analyzed at Teppi soil laboratory following standard procedures. Analysis of variance (ANOVA) and treatments separation were made by using Least Significance Difference (LSD) at 95% probability level. The analysis result indicated that there were no significance differences between Eucalyptus tree species and its adjacent open land in the level of soil nutrients (total N, available P, pH, OM, soil moisture and OC) (p